Building Roads, Building Communities: Participation and Infrastructure in Patuhu Village - Edy Sijaya; Hasman Umuri (Universitas Islam Darul Ulum Lamongan, 2026)
This study explores the dynamics of community participation in road infrastructure development in Patuhu Village, Pohuwato Regency, and the underlying factors influencing this engagement. Utilizing a descriptive qualitative method, data were gathered through observation, interviews, and literature study from key informants, including village officials and community members. The findings reveal that community participation is evident across the planning, implementation, and evaluation stages. While planning participation showed an increase during the 2025 and 2026 Musrenbang (Development Planning Deliberations), early-stage consultations (Musdus) lacked direct citizen involvement. During implementation, despite initial demands for monetary compensation, the community ultimately demonstrated strong support by voluntarily relinquishing land for the 514-meter road project. The success of this infrastructure development is driven by the community's awareness and the critical need for better agricultural access. Conversely, the study uncovers a paradox where the provision of the Village Fund (Dana Desa) inadvertently hindered participation by diminishing the traditional spirit of mutual cooperation (gotong royong), compounded by low educational levels. The research suggests that village governments must enhance direct citizen involvement in early planning and educate the public on fund allocation to revitalize community self-help.